A proton-hopping charge storage mechanism of ionic one-dimensional coordination polymers for high-performance supercapacitors. Issue 86 (16th October 2017) - Phattharasupakun, Nutthaphon; Wutthiprom, Juthaporn; Kaenket, Surasak; Maihom, Thana; Limtrakul, Jumras; Probst, Michael; Nagarkar, Sanjog S.; Horike, Satoshi; Sawangphruk, Montree
Abstract : A proton-conducting coordination polymer of Zn 2+ phosphate and protonated imidazole has been used as a novel supercapacitor material in aqueous electrolytes. Abstract : A proton-conducting coordination polymer of anionic one-dimensional (1D) chains of Zn 2+ phosphate and protonated imidazole with the formula of [Zn(HPO4 )(H2 PO4 )2 ](ImH2 )2 has been used as a novel supercapacitor material in aqueous electrolytes. This material stores charges via a proton-hopping mechanism.